1993
DOI: 10.1111/j.1476-5381.1993.tb13903.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and anti‐platelet actions of 1,2‐ and 1,3‐glyceryl dinitrate

Abstract: 1. The aim of this study was to investigate whether two metabolites of glyceryl trinitrate (GTN), 1,2 and 1,3-glyceryl dinitrate (1,2-GDN and 1,3-GDN) could account for the pharmacological effects of GTN. To this end the formation of nitric oxide (NO) from 1,2- and 1,3-GDN in the presence of bovine aortic smooth muscle cells (SMC) or endothelial cells (EC) was studied. The effects of various thiols on NO formation from these dinitrates was also evaluated. 2. 1,2-GDN or 1,3-GDN (10(-10)-10(-5) M) caused a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Chong and Fung (1991) also reported that among aliphatic and aromatic thiols tested, NAC, mercaptosuccinic acid, and TSA were the most potent generators of NO from GTN in buffer with an order of potency of NAC Ͻ mercaptosuccinic acid Ͻ TSA. Later studies then showed that this correlated with their efficacy in increasing the antiplatelet effects of GTN (Salvemini et al, 1993b) and in potentiating the in vivo hemodynamic effects of organic nitrates (Lawson et al, 1991;Salvemini et al, 1993b,c). Glutathione does not release NO and releases only nitrite, which is devoid of biological effects (except perhaps at very high doses).…”
Section: Nitric Oxide Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chong and Fung (1991) also reported that among aliphatic and aromatic thiols tested, NAC, mercaptosuccinic acid, and TSA were the most potent generators of NO from GTN in buffer with an order of potency of NAC Ͻ mercaptosuccinic acid Ͻ TSA. Later studies then showed that this correlated with their efficacy in increasing the antiplatelet effects of GTN (Salvemini et al, 1993b) and in potentiating the in vivo hemodynamic effects of organic nitrates (Lawson et al, 1991;Salvemini et al, 1993b,c). Glutathione does not release NO and releases only nitrite, which is devoid of biological effects (except perhaps at very high doses).…”
Section: Nitric Oxide Donorsmentioning
confidence: 99%
“…Glutathione does not release NO and releases only nitrite, which is devoid of biological effects (except perhaps at very high doses). Thus, glutathione does not potentiate the pharmacological actions of organic nitrates (Feelisch, 1991;Salvemini et al, 1993b).…”
Section: Nitric Oxide Donorsmentioning
confidence: 99%
“…Note that all forms of NTG delivery are prone to high-levels of inter and intra-patient variability [ 3 ]. The two main metabolites of NTG are 1,2 and 1,3-glyceryl dinitrate (1,2-GDN and 1,3-GDN), which achieve higher plasma concentrations than the parent compound but which have lower vasodilatory activity; nevertheless these metabolites contribute to the pharmacological effects of NTG administration [ 5 ].…”
Section: Current Usagementioning
confidence: 99%
“…Clinical investigations show that after ingestion, nitroglycerin cannot be detected in plasma or the concentrations are very low (16,81,83,106). Metabolites such as glycerol dinitrate are, however, detectable (57,83 (91) found that the glycerol dinitrate levels were up to 10 times higher than the nitroglycerin levels after oral and dermal administration of nitroglycerin. The plasma concentrations of glycerol-1,2-dinitrate are higher than those of glycerol-1,3-dinitrate after oral administration of nitroglycerin (81).…”
Section: Ingestionmentioning
confidence: 99%